THUNDERSTORM ACTIVITY AND LIGHTNING PROTECTION OF POWER PLANTS AND EQUIPMET ON THE TERRITORY OF AZERBAIJAN REPUBLIC - A. M. Gashimov; A. M. Khidirov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
In the article the results of a wind parameters analysis at the wind power parks construction territory in the north of the Azerbaijan Republic are presented. By means of extrapolation the  speeds  of  a  wind  stream  at  heights  of  80  and  100  m  have  been  calculated.  In  the conditions  of the  Azerbaijan  Republic  initially the  wind  potential  was  defined  at  height of 10–15 m from the earth surface by the data of the “weather vane” established at hydrome- teorological station, located within the precincts of Baku city. The subsequent measurements were spent at height of 40 m by means of “anemometer” located outside of city boundaries in a southern direction. It is established that at height of 100 m the wind speed essentially ex- ceeds the wind speed at height of 22 m. Hence, the height of 100 m is profitable for construc- tion and operation of wind constructions. Results of actual measurements have shown that wind speed depends on height and time of day. It is established that change of a wind stream within a month corresponds to change of the daily schedule of power station capacity and correlation factor of two processes appears high enough and makes 0.61. Note that for building the park of wind power plant it is necessary within 1 year continuously to spend actual meas- urements of a wind parameters at various heights (to 100 m). Otherwise placing of wind sta- tion on the given site can be not profitable. It is necessary to notice that the efficiency of wind units, besides their constructive features also depends on a correct choice of their installation place.On the other hand, the transmission of energy, produced by the wind power plants, in the power supply systems to the consumer is closely connected with a wind speed, air density, distribution of a wind stream, etc. parameters. From the told follows that research of a wind parameters represents the economic and somewhat legal value.